Cytological and histological correlation in diagnosing feline and canine mediastinal masses. (13th December 2013) - Pintore, L.; Bertazzolo, W.; Bonfanti, U.; Gelain, M. E.; Bottero, E.
<x xml:space="preserve">Abstract</x> OBJECTIVES The aim of this study was to evaluate the agreement between cytological and histological diagnosis of canine and feline mediastinal masses to assess the utility of cytological examination in accurately diagnosing and classifying mediastinal lesions. METHODS A retrospective review of 58 cases of mediastinal masses from 21 dogs and 37 cats were performed. Histopathology was used as the diagnostic reference standard. The agreement between cytological and histological diagnosis was calculated. RESULTS The complete agreement between cytological and histological classification ranged from substantial (k = 0 · 72, CI: 0 · 64 to 0 · 80) to almost perfect (k = 0 · 89, CI: 0 · 82 to 0 · 96) depending on how the cytological diagnoses classified as suspicious were used for statistical calculations. CLINICAL SIGNIFICANCE Cytological examination of canine and feline mediastinal masses is a relatively easy, low‐cost procedure, with good agreement with final histological diagnoses.